2022
DOI: 10.53771/ijbpsa.2022.3.2.0049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anticonvulsant properties of the ethanol extract of Detarium senegalense leaves in mice

Abstract: Detarium senegalense, J.F. Gmelin (Fabaceae) is used in Nigerian folk medicine to treat different diseases including epilepsy, microbial infections, gastrointestinal diseases and inflammation; its efficacy is widely acclaimed among communities in South Eastern Nigeria. The leaf extract (100 mg/kg, 200 mg/kg and 400 mg/kg) was evaluated for its anticonvulsant activity in mice. Three different study models were used; pentylenetetrazole (PTZ), brucine and isoniazid (INH) convulsion methods. The acute toxicity stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Its phytochemical analysis was equally carried out, and the result indicates the presence of a variety of phytoconstituents in the extract. These classes of chemical compounds are known to exert pharmacological effect more especially on the vital organs of the body [17,18]. Although compared to some reports, the phytochemical screening of the leaves of D. senegalense revealed the presence of a variety of secondary metabolites, including tannins (Idris, 2014), flavonoids, saponins [19], alkaloids, glycosides, steroids [20].The presence of flavonoids indicate that D. senegalensis has antioxidant and anti-diabetic activities, and the alkaloid too can be applied in the treatment of some ailment.…”
Section: Discussionmentioning
confidence: 99%
“…Its phytochemical analysis was equally carried out, and the result indicates the presence of a variety of phytoconstituents in the extract. These classes of chemical compounds are known to exert pharmacological effect more especially on the vital organs of the body [17,18]. Although compared to some reports, the phytochemical screening of the leaves of D. senegalense revealed the presence of a variety of secondary metabolites, including tannins (Idris, 2014), flavonoids, saponins [19], alkaloids, glycosides, steroids [20].The presence of flavonoids indicate that D. senegalensis has antioxidant and anti-diabetic activities, and the alkaloid too can be applied in the treatment of some ailment.…”
Section: Discussionmentioning
confidence: 99%
“…This plant contains various active principles able to inhibit the growth of mycobacteria. Previous pharmacological studies revealed that extract of D. senegalense was found to possess antidiarrhoeal activity [10], antimicrobial activity [11,12], and antiproliferativ activity [13], anthelminthic [14], antiepileptic [15] and antihyperglycemia [16]. The present study investigates the hepatotoxicity potential of ethanol stem bark extract of Detarium senegalense against paracetamol induced hepatotoxicity in albino rats.…”
Section: Introductionmentioning
confidence: 94%